2021
DOI: 10.1101/2021.05.15.21257261
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Systematic Review and Meta-analysis on COVID-19 Vaccine Hesitancy

Abstract: Background: The presented meta-analysis was developed in response to the publication of several studies addressing COVID-19 vaccines hesitancy. We aimed to identify the proportion of vaccine acceptance and rejection, and factors affecting vaccine hesitancy worldwide especially with the fast emergency approval of vaccines. Methods: Online database search was performed, and relevant studies were included with no language restriction. A meta-analysis was conducted using R software to obtain the random effect mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…Previous studies conducted in the general population have shown variable rates of COVID-19 vaccine hesitancy globally, but generally fairly large rates in different regions of the world [11,12]. According to a Center for Disease Control and Prevention report released in October 2022, 68.2% of the world population received at least one dose of the vaccine and a suboptimal proportion of the world population has been fully vaccinated [13].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies conducted in the general population have shown variable rates of COVID-19 vaccine hesitancy globally, but generally fairly large rates in different regions of the world [11,12]. According to a Center for Disease Control and Prevention report released in October 2022, 68.2% of the world population received at least one dose of the vaccine and a suboptimal proportion of the world population has been fully vaccinated [13].…”
Section: Introductionmentioning
confidence: 99%
“…6 Worldwide, the low vaccine uptake intention or hesitancy towards a particular vaccine has been recognized the most common phenomenon among the student groups in previous vaccination programs such as for influenza vaccination, [7][8][9][10][11] human papilloma virus (HPV) vaccination, [12][13][14][15][16] hepatitis B vaccinations, 17,18 pertussis vaccinations, 19 HIV vaccinations, 20 measles vaccinations, 21 and now COVID-19 vaccinations. 22 In context of current COVID-19 pandemic, most of the review studies on vaccine hesitancy were conducted by analyzing the general population sample [23][24][25][26][27][28][29] and few emphasized the regional locations. [30][31][32] Although a study attempted to illustrate the COVID-19 vaccine hesitancy among health care student trainees; 33 there is lack of evidence that concentrated to assess COVID-19 vaccine hesitancy among the students globally.…”
Section: Introductionmentioning
confidence: 99%
“…19 Aboelsaad et al also indicated that the difference in acceptance or non-acceptance of the vaccine is affected by the influence of the vaccine and its side effects. 20 In a study, Shekhar et al examined people's acceptance of the COVID-19 vaccine and concluded that the possible side effects were the most common concern of people after vaccination. 15 In another study, Bono et al mentioned side effects as a factor of doubt in accepting the COVID-19 vaccine, 16 which is in line with the results of the present study.…”
Section: Discussionmentioning
confidence: 99%